Recovery of Plastic Waste in Eco-Construction: Case of Brick Making - Ali, Abakar; Mahamat, Abdallah Dadi; Tchou, Harry Brahim (European Journal of Applied Sciences, 2023)
In this research work, we propose to recover plastic waste in construction. To do this, they are melted and mixed with sand. The sand-plastic mixture is mixed until a homogeneous paste is obtained, which is molded while hot and unmolded approximately ten (10) minutes after cooling. In order to choose an optimal (sand-plastic) dosage. Four formulations were made: 100% plastic, 60%S+40%P, 55%S+45%P and 50%S+50%P. The 50%S+50%P formulation gave better results in terms of the quality of the materials produced(with S: sand and P: plastic). These results are justified by the compressive strength of between 3.96 and 5.38 MPa. The flexural strength ranging from 1.23 to 1.72 MPa, an absorption rate of 0.66% and a negligible coefficient of thermal expansion. The cooking time varies from 25 min to 21 min depending on the formulation. The mixing time varies from 49 to 60 min and the demolding time varies from 11 to 23 min. The production price of a plastic waste brick is 322.5 FCFA.